Analysis of erythrocytes in oral submucous fibrosis - A morphometric study - Vijay Wadhwan; Arvind Venkatesh; Preeti Sharma; Sangeeta Malik; Chitrapriya Saxena (Wolters Kluwer Medknow Publications, 2021)
Background: Oral submucous fibrosis (OSMF) is a chronic progressive scarring oral disease caused due to areca quid chewing. The constituents of areca nut can enter into the circulation by swallowing the liquid mixture of areca quid which evokes oxidative stress on RBC membrane integrity. Aims: To study the morphometric characteristics of erythrocytes under light microscopy and to assess the role of areca quid constituents on the morphology of circulating erythrocytes. Materials and Methods: Peripheral blood smears prepared from blood samples of 50 patients selected according to Lai's classification. Group I: Normal individuals (10 cases); Group II: Mouth opening > 35 mm (10 cases); Group III: Mouth opening 30-35 mm (10 cases); Group IV: Mouth opening 20-30 mm (10 cases) and Group V: Mouth opening < 20 mm (10 cases). The slides were stained with Leishman's stain and assessed by light microscopy. A total of 100 randomly selected RBCs from 5 different fields in each smear were selected and the RBC circumference was measured and tabulated. Statistical analysis and Results: Data was analyzed using GraphPad Prism 5.03 software. Tukey's multiple comparison test showed statistically significant difference (p < 0.05) between groups I and IV; I and V; II and IV; II and V; III and IV; III and V. Conclusion: These results suggest the possibility of cytotoxic effect of areca quid constituents on circulating erythrocytes in advanced cases of OSMF, which might result in microcytic anaemia.